Je sais pourquoi chante l'oiseau en cage - Angelou, Maya; Besse, Christiane (Le Livre de poche, 2012)
« Dans ce récit, considéré aujourd'hui comme un classique de la littérature américaine, Maya Angelou relate son parcours hors du commun, ses débuts d'écrivain et de militante dans l'Amérique des années 1960 marquée par le racisme anti-Noir, ses combats, ses amours. Son témoignage dénué de la moindre complaisance, révèle une personnalité exemplaire. À la lire, on mesure mieux encore le chemin parcouru par la société américaine en moins d'un demi-siècle. »-- Quatrième de couverture.
Keywords: 1900-1999; afro-féminisme; amériques; antiracisme; approches et analyses; arts; biographie; cours; discipline; féminisme afroaméricain; lit2815; premier cycle; périodes historiques; racisme; régions géographiques; systèmes d'oppressions; thématiques; écriture des femmes*; états-unis; études littéraires

Life notations of Daisy Sweeney: Reflections of othermothering, musicianship and Montreal - Campbell, Arlene (Université York, 2012)
The life story of Mrs. Daisy Sweeney, an African Canadian native of Montreal, Quebec, helps fill a void in the historical documentation of Montreal Blacks (especially female elders). Of particular significance is her prominence as a music educator and othermother during her life. The current literature on African Canadian othermothering experiences is not synonymous with both White or African American females and inclusion of their voices in academic, as well as mainstream spaces, is virtually non-existent. This dissertation asks: What did it mean to be a first generation 'Negro' working class bilingual female in a largely hostile White francophone Quebec metropolis in the early 20th Century? How can her narratives help shape and inform life history and African Canadian othermothering research? My sojourn with Mrs. Daisy Sweeney referenced African centered epistemology in my conceptual understanding of herself and community mothering. Capturing her conversations meant engaging with multiple methodologies articulated through African oral traditions, life history, archival canons and interdisciplinary inquiries. It is striking to note that there were not only certain tensions associated with memory loss and physical limitations (prompted by the aging process) that destabilized and enriched our 'interactive' communication, but also revealed a rupture and reversal of the participant/researcher dynamic. In spite of blatant racial discrimination that plagued Montreal's Black communities during that time, Daisy Sweeney fulfilled a life-long dream and taught hundreds of children the canon of classical piano for over 50 years. She lived her voice through her music, finding ways to validate her own identity and empowering others in the process. She used the musical stage as her platform to draw invaluable connections between race, gender, language and social class. Daisy Sweeney's generation of othermothers is dying out and, as the carriers of culture, the urgency to tell their stories must be emphasized. The account respects, reclaims and reflects those voices. It is time to write in African Canadian female elders and diversify the exclusionary genre of life history and archival research.
Keywords: 1900-1999; DIG; afro-féminisme; amériques; approches et analyses; discipline; femmes* noires; histoire et politique; maternité; montréal; musique; mémoires/thèses; philosophie; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; travail

Polyrhythmic dance currents: Race multiculturalism and the montreal dance community - Templeton, Melissa (Université de Californie à Riverside, 2012)
This dissertation examines African and African Diaspora concert dance in Montreal in relation to Canadian multicultural policies and Québec nationalism. The multiple layers of colonization and various waves of immigration to Québec have made the province a unique nation with its own complex history of racial construction, quite unlike the racial histories of the U.S. or the rest of Canada (though still greatly informed by these racial paradigms). In the debates that arise in Québec over multiculturalism, language is often seen as the main cultural component in need of preservation. However, this focus on language often masks other elements at play in these cultural debates, in particular, how "race" informs notions of cultural belonging in Québec. A focus on African Diaspora dance in Montreal (Québec's largest and most demographically varied city) helps bring racial construction to the fore for two reasons. First, language differences do not distinguish Québec's Black community from the white French-Canadian majority as Québec's Black population is comprised mainly of French-speakers, and accordingly, studying Montreal's African Diaspora reduces the significance of linguistic difference. Second, concentrating on dance practices helps identify how the Montreal public interprets bodies and their cultural meanings. By analyzing the public support and critical reception of African Diaspora dance practices in Montreal, this dissertation examines how racial difference is constructed through multicultural rhetoric, policies, and debates about dance; it also suggests that dance practitioners have the ability to change and inform these constructed identities and the social landscape that frames them. To conduct this research, I use archival material along with personal interviews and participant-observer ethnography to examine: the early visits of Les Ballets Africains to North America (with a particular focus on Montreal); the Montreal-based company Les Ballets Jazz; the 1999 Montreal festival Afrique: Aller/Retour; and the work of Contemporary African dance choreographer Zab Maboungou. With these subjects, my projects contributes a partial history of African Diaspora dance in Montreal and analyzes the effectiveness and the shortcomings of Canadian Multiculturalism on this community.
Keywords: 1900-1999; amérique du nord; amériques; approches et analyses; canada; corps; corps féminin; danse; diaspora africaine; discipline; montréal; multiculturalisme; mémoires/thèses; philosophie; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques